Terminology of didactic wisdom in the ancient Israelite scribal schools as presented in Proverbs 1:1–7 - Mandey, Jenry 1992-; Sindoro, Pujiastuti E. (2025)
Proverbs 1 verses 1-7 encompasses an important section of the Hebrew bible related to ancient didactic wisdom terminology. This article analyses the Masoretic Text in Hebrew to categorise and examine the terminology concerning the theory of the scribal schools that developed in ancient Israel. The issue is the absence of an undisputed indication of the text’s Sitz im Leben . Consequently, the proposal concerning the Sitz im Leben in this text pertains to the scribes. The employed method is textual exegesis, aimed at investigating the text’s background through historical analysis. The study is conducted by examining the terms in each verse, considering their textual meaning and historical contexts, with an emphasis on their usage in scribal schools, to reveal the text’s historical background. Intradisciplinary and/or interdisciplinary implications: This study examined the significance and application of educational terminology in ancient Israel as presented in the introductory passage of the book of Proverbs. This article contributes to historical studies of the ancient education system and biblical studies.
Keywords: Hebrew Proverbs; Mishle Shlomo; didactic wisdom; scribal schools; Scribes